Approximation for Certain Stancu Type Summation Integral Operator (Analysis in Theory and Applications, 2018)
In the present paper, we consider Stancu type generalization of the summation integral type operators discussed in [15]. We apply hypergeometric series for obtaining moments of these operators. We also discuss about asymptotic formula and error estimation in terms of modules of continuity.